Screening constant by unit nuclear charge calculations of resonance energies and widths of the 3pns 1, 3P° and 3pnd 1P° Rydberg series of Mg-like (Z=13-26) ions. (January 2017) - Khatri, Indu; Goyal, Arun; Diouldé Ba, Mamadou; Faye, Maurice; Sow, Malick; Sakho, Ibrahima; Singh, A.K.; Mohan, Man; Wagué, Ahmadou
Abstract: Resonance energies and total natural width of the 3p n s 1 P° and 3p n d 1 P° Rydberg series of Mg-like ( Z =13–26) ions are reported. Resonance energies of the Mg-like Al + belonging to the 3p n s 3 P°→ 2 p 3 6 p P 1 / 2 0 2 and 3p n s 3 P°→ 2 p 3 6 p P 3 / 2 0 2 transitions are also tabulated. The calculations are made in the framework of the Screening constant by unit nuclear charge (SCUNC) formalism. Excellent agreements between experiments at ALS and R -matrix calculations are obtained for both 3p n s 1, 3 P° and 3p n d 1 P° Rydberg series of the Mg-like Al + ions. The present results for Mg-like Si 2+, S 4+, Cl 5+, and Ar 6+, compared with the only existing R -matrix calculations indicate lack of accuracy in the Mg-like Si 2+ data obtained from noniterative formulation of the eigenchannel R- matrix method. New precise data for Mg-like P 3+, K 7+, Ca 8+, Sc 9+, Ti 10+, V 11+, Cr 12+, Mn 13+, and Fe 14+ ions are presented as useful guidelines for investigators focusing their challenge on the Photoionization of Mg-like heavy charged ions in connection with their application in laboratory, astrophysics, and plasma physics. Highlights: Resonance energies and width of 3p n s 1, 3 P° and 3p n d 1 P° series of Mg-like ( Z =13–26) ions reported. Excellent agreements between experiment and theory. New precise data for Mg-like P 3+, K 7+, Ca 8+, Sc 9+, Ti 10+, V 11+, Cr 12+, Mn 13+, and Fe 14+ tabulated. Useful benchmarked data for application in laboratory, astrophysics, and plasma physics.